Implementation of Group Guidance Cognitive Behavior Therapy Approach to Deal With Bullying Behavior At Smp It Darul Ma'arif - Lutfiyatut Tamamiyah (Jurnal Indonesia Sosial Teknologi, 2024)
This thesis discusses the implementation of a group guidance cognitive behaviour therapy approach to deal with bullying behaviour in SMP IT Darul Ma'arif, where there are class students who commit bullying behaviours such as calling their friends inappropriately, bullying their friends inside and outside the classroom; mocking other students' physiques; hitting each other; and And students often mock the names of their friends' parents. The purpose of this study was to determine the impact of bullying on students at SMP IT Darul Ma'arif and to determine the implementation of group guidance on the Cognitive Behavior Therapy (CBT) approach to dealing with bullying behaviour at SMP IT Darul Ma'arif. This study uses qualitative research with a type of phenomenological research, where this study aims to understand and describe a specific phenomenon that is deep and obtains the essence of participants' life experiences with the phenomenon. The data used are primary and secondary. Data collection tools are observation methods, interviews, and documentation. Meanwhile, in data processing and analysis, the steps used are data reduction, data presentation, and conclusions. Based on the results of the study, it is known that group guidance services for the Cognitive Behavior Therapy (CBT) approach to dealing with bullying behaviour at SMP IT Darul Ma'arif have decreased bullying behaviour. Group guidance services The Cognitive Behavior Therapy (CBT) approach is effective in dealing with bullying behaviour at SMP IT Darul Ma'arif, as evidenced by the presence of students who no longer bully their friends.